Youth Activism: How Demographic Factors Affect Participation in Activism Among Young Adults and How that Compares to Older Adults - Best, Jennifer (Tufts Archival Research Center, 2022)
Only 52-55% of young people aged 18-29 voted in the 2020 Presidential Election, compared to 66.2% of all eligible voters who voted, yet young people make up a significant proportion of electoral campaigns and other activist spaces, including mutual aid groups, protests, and more. My thesis aims to narrow the gap in the literature by investigating what demographic factors affect which young people are engaged in activism and why. Besides age, the four primary demographic categories I investigated were race, gender, education, and income. I used the 2020 Cooperative Election Survey to determine rates of participation in various forms of activism, including general activism, campaigning, protesting, and donating. I also fielded a survey of former 2020 Ed Markey for U.S. Senate Campaign fellows, which allowed me to build on the quantitative aspects of the CES with qualitative reasons as to how people saw their demographic backgrounds affected their decision to become involved in activism. Through my research, I found that while young people are just as likely to participate in activism as older people, youth activists are the ones doing the more difficult and time-consuming forms of activism, such as campaigning and protesting, whereas older activists are participating in the easier and less time-consuming forms of activism, such as donating.; Thesis (B.A.)--Tufts University, 2022.; Submitted to the Dept. of Political Science.